Pathological Changes of Immunized Rabbits with proteus vulgaris Fimbriae Antigen - Faleh, Enaam Bader (The Iraqi Journal of Veterinary Medicine, 2011)
The study was carried to investigate pathological effects of fimbrial antigen of proteus vulgaris 20 rabbit has been divided into (4) equal groups The first group immunized subcutaneous twicely with (01) ml of pv fimberial Ag (200 μ/ml) with 2 week interval the second group was treated as the 1st group but in a dose containing 100 μ/ml. Third and fourth group considered as positive and negative control groups respectively. After 45 days post immunization first second and third groups were challenged with 01ml of bacteria suspension contain (107x5cfu/ml) of virulent pvulgaris. All rabbits of the third group died during 24-48 hr post challenge with severe congestion in all internal organs associated with necrotic foci mainly in liver and kidney at days 3-20 post challenge immunized infected rabbits (died and survival) were sacrified histopathologically the third group showed focal necrosis and polymorphonuclear cells (PMNCs) infiltration in liver parenchyma pulmonary edema with severe congestion and depletion of spleen Mild pathological changes were revealed in the 1st and 2nd immunized groups characterized by kupffer cell proliferation dilation of sinusoids with mononuclear cells (MNCs) aggregation (mainly lymphocyte) around blood vessels lymphoid hyperplasia in spleen with hyperplasia of goblet cells and secretion of mucin in the intestine mainly in the first groupfimberial antigen considered as effective immunogen for protecting rabbits against p volgaris infection and it is synchronized with dose of this antigen.